(untitled) (Bangladesh Critical Care Journal, 2021)
Background: Last two decades have witnessed a steady improvement in the quality of perinatal care in Bangladesh. Around 4-8% of all live births are very low birth weight (VLBW) & low birth weight (LBW)is 10.6%. The present study was done to determine risk factors, complications and immediate outcome in VLBW babies. Methods: It was a prospective cohort study conducted in a level-III NICU of Ad-din Hospital over two years period (April 2019-March 2021). 356VLBW babies (birth weight <1500 g) were assessed for demographic characteristics, risk factors (both maternal & fetal) and neonatal complications. The American Academy of Pediatrics protocol for neonatal resuscitation was followed for the management of VLBW. Screening for retinopathy of prematurity was done. Data were entered in predetermined proforma and statistical analysis was done. Results: Out of 356 VLBW babies, 268 (75.2%) survived. Maternal risk factors associated with birth of VLBW babies were primiparity (46.8 %), poor socio-economic status (40.86%), multiple gestations (36.83%), Premature rupture of membrane (PROM) (21.6 %), hypertension (20 %) and under nutrition (17 %). Significant morbidities were found Jaundice (43.31%), Respiratoy Distress Syndrome (RDS) (28.08 %), apnoea (26.34%), birth asphyxia (20.43%), and sepsis (22.5 %). Mortality was higher among males (20.43%) than females (12.9%). None below 26 weeks of gestation and birth weight of 750g survived. RDS was the main cause of death (46.15%) followed by birth asphyxia (23%), sepsis (19.2%) and Intraventricular Haemorrhage (IVH) (11.5%). Antenatal steroid improved the survival (77.4%) and reduced the incidence of RDS, Necrotizing Enterocolitis (NEC) and IVH. Retinopathy of Prematurity (ROP) was detected in 30.9 % VLBW babies. Conclusions: Higher birth weight, gestational age, female sex and antenatal steroids improved survival amongst babies. Antenatal steroids reduced incidence of RDS, NEC and IVH when preterm delivery was inevitable. Judicial use of supplemental oxygen and blood products prevent development of ROP. Bangladesh Crit Care J September 2021; 9 (2): 94-100